Pengembangan Media TaKeru Sebagai Media Pembelajaran Berbasis Literasi Matematika - Ahmad Choirul Anam; Diyah Ayu Rizki Pradita; Nanda Ayu Indarasati; Wardani Wardani (Jurnal Tadris Matematika, 2022)
TaKeru media was a digital and manual-based learning media that aimed to improve students' understanding of the subject matter of curved side spaces, especially tubes and cones. These study aimed to develop TaKeru media as an effective learning medium to be applied as research subjects to class IX junior high school students. This study used Research and Development (R and D) methods, and ADDIE (Analysis, Design, Development, and Evaluation) development procedures. The data analysis technique used in this study was descriptive data analysis technique, which described the validity, practicality, and effectiveness of the TaKeru media using t-test. The instrumens used in this study were media validation sheets, test sheets, and student response questionnaires for eight students. The results showed that 80% of the participants showed a positive response, and student learning outcomes also increased, indicated by the value of t count = 5.635> t table = 2.365, with a significance level of 5%. Based on the increase in learning outcomes and positive responses from students, TaKeru Media as a learning media based on mathematical literacy is valid, practical, and effectively applied to teach curved side spaces (tubes and cones).